ΑΛΚΙΒΙΑΔΗΣ ΠΟΛΥΤΡΟΠΟΣ. CONSIDERACIONES EN TORNO A LA VALORACIÓN Y LA CARACTERIZACIÓN DE LOS PERSONAJES EN LA HISTORIOGRAFÍA DEL SIGLO IV - Campos Daroca, Javier; López Cruces, Juan Luis (Myrtia, 1990)
The assessment of Alcibiades conveyed by the fragment 288 from Theopompus’ ’Hellenica’ (’FGrHist’ 115) remains not adequately treated in modern historiographical research. This paper tries to put forward an interpretation of Theopompus’ characterization of Alcibiades based on two points that are closely interrelated: ’polytropía’ and exile. Greek views on both topics are adduced in order to elicit Theopompus’ originality in his presentation on Alcibiades and to reject from it too eschematic moralizing criteria.